The impact of housework participation on prosocial behavior development among junior high school students in China - Jin Zhao; Huirong Tuo (Scientific Reports)
Abstract This study examines the effect of housework participation on the development of prosocial behaviors among students in China. Using data from the China Education Panel Survey, a nationally representative survey of 8678 students at 221 classes in 28 counties, we employed two identification strategies (i.e., the OLS model and IV model) to overcome the endogeneity of housework participation. Our analysis reveals a significantly positive effect between housework participation and prosocial behavior development. The mechanism analysis indicated that compared to nonparticipator, students who participate in housework tend to develop a higher level of positive emotions, more parental supervision, and a closer parent-child relationship. We also find that most of these effects are more prominent for disadvantaged groups (males and left-behind). Our study underscores the need for policies and interventions aimed at promoting housework participation habits and actions to enhance students’ behavior development in educational settings.